Ukufa kukaShaka. - Zondi, Elliot (Wits University Press, 2021)
Ukufa kukaShaka is a historical drama in isiZulu. Based on the events surrounding the assassination of Shaka, the mighty Zulu king, by his two half-brothers, Dingane and Mhlangana, aided and abetted by his paternal aunt, Mkabayi, in 1828. In the play Elliot Zondi explores the classic theme of the tragic hero's fatal flaws.